KEARIFAN LOKAL PETANI DAN KELESTARIAN GAMBUT (Studi Kasus: Desa Lukun Kecamatan Tebing Tinggi Timur Kabupaten Kepulauan Meranti Provinsi Riau) - Seger Sugiyanto; Ashaluddin Jalil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Fires in 2015 and 2018 in the village of Lukun burned a total of about 310 hectares have serious consequences for nature and the local social environment. In addition to making some people lose their livelihoods, fires have also caused fauna migration and plant death. Furthermore, Peatland in Lukun Village has become critical and has even drought. By using the snowball technique, the author found 7 informants they are 3 sago farmers, 2 rubber farmers, 1 areca nut farmer, 1 vegetable farmer and banana. The type of research used was qualitative descriptive with 2 months of research duration. The findings of the study in terms of land preparation methods used are clear-cutting and cutting down the hallway. After a few days later, they start to burn the remaining wood or leaves. The Land cultivation and the seeds procurement are carried out with a system of "replacements" between the fellow farmers. How to care for the plant is still in the traditional way which uses human hair as a pest barrier pig, does fumigation to eliminate the pest beetles, and cutting the bush to avoid wild animals. The activities of farmers still use simple technology and equipment such as machetes, hoes, axes, carts and others. Ways of farming are still in the form of traditional. It is done to preserve peat as well as cultural heritages of the past and disseminated through two forms of the fieldwork and discussions. In addition to taking local wisdom of farming, farmer awareness on the preservation of peat indicated by the start of an environmentally friendly plant such as fruits or timber and joined a group of MPA in the region of Lukun.Keywords: Local Wisdom, Farmers, Peat Sustainability